Earnings Management and Tax Avoidance in Determining Firm Value in the Financial Sector - Agustin, Agustin; Syamsul, Syamsul; Zuhroh, Siti (International Journal Of Economics Social And Technology (IJEST), 2025)
This study explores the role of earnings management and tax avoidance in determining firm value within the financial sector in Indonesia. Employing a causal associative method with a quantitative approach, the research analyzes 68 observations from 41 financial companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. Earnings management is measured using the Modified Jones Model, tax avoidance through the Cash Effective Tax Rate, and firm value by Tobin’s Q. Data were analyzed using multiple linear regression, supported by classical assumption tests. The findings indicate that neither earnings management nor tax avoidance has a significant impact on firm value, whether assessed individually or simultaneously. This may be attributed to strict regulatory oversight and the increasing investor focus on business fundamentals rather than accounting or tax strategies. The study highlights limitations, such as a short observation period and reduced sample size due to data cleaning. Future research is encouraged to include additional variables, extend the time frame, and consider sector-specific analyses to enhance understanding. The results provide practical insights for corporate stakeholders and contribute to academic discourse on financial reporting and firm valuation in regulated markets.